Thermal and optical properties of La2O3–Ga2O3– (Nb2O5 or Ta2O5) ternary glasses. Issue 8 (22nd February 2018) - Yoshimoto, Kohei; Masuno, Atsunobu; Ueda, Motoi; Inoue, Hiroyuki; Yamamoto, Hiroshi; Kawashima, Tatsunori
Abstract: La2 O3 –Ga2 O3 – M 2 O5 ( M = Nb or Ta) ternary glasses were fabricated using an aerodynamic levitation technique, and their glass‐forming regions and thermal and optical properties were investigated. Incorporation of adequate amounts of Nb2 O5 and Ta2 O5 drastically improved the thermal stabilities of the glasses against crystallization. Optical transmittance measurements revealed that all the glasses were transparent over a wide wavelength range from the ultraviolet to the mid‐infrared. The refractive indices of the glasses increased and the Abbe number decreased upon substituting Ga2 O3 with Nb2 O5, and the decrease in the Abbe number was significantly suppressed when Ta2 O5 was incorporated into the glass. As a result, excellent compatibility between high refractive index and lower wavelength dispersion was realized in La2 O3 –Ga2 O3 –Ta2 O5 glasses. Analysis based on the single‐oscillator Drude–Voigt model provided more systematical information and revealed that this compatibility was due to an increase in the electron density of the glass.